(untitled) (American Journal of Management, 2025)
A presentation of five land administration programs since the 1990s highlights the success and failure factors encountered. Each program is accompanied by references available on the web. The projects aim to link two components: a systematic inventory of land occupancy, i.e. a technical and social aspect, and the registration of related rights, i.e. a legal aspect. Official reports do not clearly mention the factors that have contributed to the results, which are classified as satisfactory or unsatisfactory. Quality assurance systems are often weak or non-existent, leading to delays or blockages. Sometimes these deficiencies result from project management or local governance, without the donor’s involvement. The absence of appropriate governance can also be felt in properly selecting companies awarded tenders, good coordination of local components such as the Cadaster and Land Register or sometimes cost monitoring.